MATH SOLVE

3 months ago

Q:
# got stuck on finding property “a” in said polynomial

Accepted Solution

A:

Answer:Hence, in the simplification of [tex](y -3)(y^2 +3y + 9)[/tex] the value of a = 9.Step-by-step explanation:Here, the given expression is [tex](y -3)(y^2 +3y + 9)[/tex]Simplify this given expression, we get:[tex](y -3)(y^2 +3y + 9) = y)(y^2 +3y + 9) -3(y^2 +3y + 9)\\= y(y^2) + y(3y) + y(9) -3(y^2) -3(3y) -3(9)\\=y^3 + 3y^2 + 9y - 3y^2 -9y - 27\\\implies y^3 - 27 = 0\\[/tex]Now, the given expanded form is [tex]y^3 + 3y^2 + ay - 3y^2 -ay - 27[/tex]Comparing it with given second last step in simplification, we get[tex]y^3 + 3y^2 + ay - 3y^2 -ay - 27 = y^3 + 3y^2 + 9y - 3y^2 -9y - 27[/tex]Comparing all term on both sides, we getay = 9yand -ay = -9y⇒ a = 9 on both sides.Hence, in the simplification of the polynomial, the value of a = 9.